Answer: 10
Step-by-step explanation: you have to simplify for it to equal 10
Answer:
8x^{4}-2/3x^{2}-2/3x
Step-by-step explanation:
Answer:
a) 4(t - r) = 4(6 - 2.5) = 4 x 3.5 = 14
b) 4t - r = (4 x 6) - 2.5 = 24 - 2.5 = 21.5
c) 2(3t - 10) = 2(3 x 6 - 10) = 2(18 - 10) = 2 x 8 = 16
d) (t - 2)² = (6 - 2)² = 4² = 4 x 4 = 16
e) cannot decipher the equation
f) 6r + t = 6 x 2.5 + 6 = 15 + 6 = 21
<span>4x</span>² <span>+ 13x + 3=
4x</span>² + 12x + x + 3 =
4x(x+3) + (x+3) =
(4x+1)(x+3)
Answer:
Step-by-step explanation:
Do percent Proportions
23,750 x
______
______ 100
5
Cross multiply
23,750×100= 2375000
5×x= 5x
2375000÷5+
idk sorry